Safety, tolerability and immunogenicity of a condensed, multi-dose prime regimen of PfSPZ Vaccine for the prevention of Plasmodium falciparum malaria infection - Andrea A. Berry; Thomas L. Richie; L. W. Preston Church; Matthew B. Laurens; Colleen Boyce; Natasha KC; Sudhaunshu Joshi; Abra Rachida Koudjra; Lauryn Butler; Mei-Chun Chen; Yonas Abebe; Tooba Murshedkar; et al. (Malaria Journal)
Abstract Background The World Health Organization (WHO) has called for new malaria vaccines with > 90% efficacy against Plasmodium falciparum infection to expand the anti-disease benefit provided by the RTS,S/AS01 and R21/Matrix M subunit vaccines currently administered to infants and young children in sub-Saharan Africa. Attenuated P. falciparum sporozoites (PfSPZ) are being developed as a traveller’s vaccine and to fulfill WHO’s call for high-level efficacy in endemic countries to support malaria elimination. Methods PfSPZ Vaccine, comprised of radiation-attenuated PfSPZ, was compared with normal saline placebo in a randomized, double-blind trial targeting 60 malaria-naive US adults to assess safety, tolerability, immunogenicity, and efficacy against heterologous controlled human malaria infection three and twelve weeks after immunization. Pharmacists provided syringes to blinded clinicians using 3:1 (vaccine:placebo) blocked randomization, for administration by direct venous inoculation on days 1 and 8 (multidose prime) and day 29 (boost), a condensed regimen with superior efficacy. Primary outcomes included adverse events and antibody responses to the P. falciparum circumsporozoite protein (PfCSP). Results 31 participants were screened, randomized and immunized twice (V1, V2) 5–7 days apart, with one withdrawal after an intercurrent adverse event. A vial issue, later traced to the vial manufacturer, halted further immunizations. Solicited local and systemic adverse events recorded for 2 and 7 days after immunizations, respectively, occurred with equal frequency and severity in the 23 vaccinees and 7 controls receiving two immunizations, as did unsolicited adverse events recorded for 28 days and laboratory abnormalities 1 and 5 weeks after V2. Four of 23 vaccinees and one of 7 controls (p = 1.00) developed grade 2 adverse events including subjective fever, headache, malaise, fatigue, rigors, arthralgia and myalgia after V2 but not V1, these symptoms generally resolving within 24 h. Twenty-two of 23 (96%) vaccinees developed IgG (median 99-fold increase over baseline) and IgM (median 1,110-fold increase) antibodies to PfCSP one week after V2. Antibody responses were not associated with reactogenicity. Conclusions The two-dose priming immunization regimen was safe, well tolerated and highly immunogenic. Larger studies may better define the adverse event profile of condensed regimens of PfSPZ Vaccine in malaria-naive adults. Trial registration number: clinicaltrial.gov NCT05604521.